Sustainable Energy for Smart Cities : First EAI International Conference, SESC 2019, Braga, Portugal, December 4–6, 2019, Proceedings /: First EAI International Conference, SESC 2019, Braga, Portugal, December 4–6, 2019, Proceedings. (2020) - Unknown
No abstract available